Analisis multidimensional konflik agraria di Desa Lhok Gajah dalam perspektif sosiologi - Br Matanari, Thamara Putriani; Azwar, Welhendri; Jamil, Muhamad (Dimensia: Jurnal Kajian Sosiologi, 2026)
Marginalized communities often face structural barriers that hinder their access to the same resources, services, and opportunities as other communities. They tend to experience discrimination, oppression, and inequality in various aspects of life, making empowerment necessary to reduce such marginalization. This study aims to analyze indicators of marginalization in the community of Lhok Gajah Village through the perspectives of conflict, functionalism, interpretivism, and critical theory. The study employs a field research approach using thematic analysis. The findings reveal that agrarian conflicts in Lhok Gajah Village, Southwest Aceh, reflect the complexity of social, economic, and political dynamics involving various actors with differing interests. The conflict perspective highlights structural injustice in access to resources; functionalism views conflict as a threat to social stability; interpretive theory emphasizes social construction; while critical theory critiques structural injustice as the root of agrarian conflict in society.